Mobilities, Tourism and Travel Behavior Contexts and Boundaries - Butowski, Leszek (IntechOpen, 2018)
The notion of "mobilities," when looked at from a practical point of view, turns out to cover different kinds of human activity. It is not surprising, then, that when approached from an academic perspective, it reveals enormous potential for interdisciplinary research, which has proven extremely attractive to many scholars from different continents, disciplines, and schools of academic inquiry. The scholars in this volume focus on the specific aspects of mobilities, namely, tourism and travel behavior, but approach them from a plethora of positions. Such a myriad of perspectives is bound to be challenging in methodological terms, but it seems there is a growing agreement as to the worthiness of this interdisciplinary research. By means of combining various approaches, researchers obtain access to a fascinating and increasingly ubiquitous phenomenon of contemporary human mobility.